Functional surfaces obtained from emulsion polymerization using antimicrobial glycosylated block copolymers as surfactants. Issue 34 (14th September 2015) - Álvarez-Paino, Marta; Muñoz-Bonilla, Alexandra; López-Fabal, Fátima; Gómez-Garcés, José L.; Heuts, Johan P. A.; Fernández-García, Marta
<x xml:space="preserve">Abstract</x> Antimicrobial surfaces were obtained from latex particles stabilized with amphiphilic block copolymer surfactants containing both quaternary ammonium and carbohydrate groups.